An integrative analysis of chemically-induced cirrhosis-associated hepatocarcinogenesis: Histological, biochemical and molecular features - Romualdo, Guilherme Ribeiro [UNESP]; Grassi, Tony Fernando [UNESP]; Goto, Renata Leme [UNESP]; Tablas, Mariana Baptista [UNESP]; Bidinotto, Lucas Tadeu; Fernandes, Ana Angélica Henrique [UNESP]; Cogliati, Bruno; Barbisan, Luís Fernando [UNESP] (Elsevier, 2017)
This study aimed the integrative characterization of morphological, biochemical and molecular features of chemically-induced cirrhosis-associated hepatocarcinogenesis. Thus, male Wistar rats were submitted to a diethylnitrosamine (DEN)/thioacetamide (TAA)-induced model. Liver tissue was processed for global gene expression, histopathological and collagen evaluations; as well as immunohistochemical and oxidative stress analysis. Gene Ontology and functional analysis showed the upregulation of extracellular matrix deposition genes, such as collagen type I alpha 1 and 2 (Col1α1 and Col1α2) and tissue inhibitor of metalloproteinase 1 and 2 genes (Timp1 and Timp2). In agreement these findings, animals presented extensive liver cirrhosis with increased collagen deposition (Sirius red). Besides, the animals developed many glutathione S-transferase pi (GST-P)-positive preneoplastic lesions showing high cell proliferation (Ki-67), in keeping with the Gstp1 and Gstp2 increased gene expression. DEN/TAA-treated rats also showed the upregulation of tumorigenesis-related annexin A2 gene (Anxa2) and few neoplastic lesions (hepatocellular adenomas, carcinomas, and cholangiocarcinoma). In contrast, gene expression and activity of antioxidant enzymes were decreased (glutathione peroxidase, total glutathione-S-transferase, and catalase). The model featured remarkable similarities to human hepatocarcinogenesis. Our findings could bring up new molecular insights into cirrhosis-associated hepatocarcinogenesis, and provide a suitable animal model for the establishment of further diagnostic, preventive and therapeutic approaches.
Keywords: Diethylnitrosamine; Hepatocarcinogenesis; Liver cirrhosis; Oligo microarray; Thioacetamide; Wistar rats